IMPACT OF NAPHTHALENE EXPOSURE ON MARKER ENZYMES OF GREEN MUSSEL Perna viridis - GOPI, J.; NATHIYA, K. RUPA; DEVI, A. SRI; KRISHNAMURTHY, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Backgrounds: Environmental contamination has been increased in recent decades as a result of the fast expansion of anthropogenic activities, particularly in the aquatic ecosystem. Under a range of severe environmental circumstances, marine organisms can be susceptible to oxidative stress and results in the changes in the biochemical components which can be assessed to know the health status of organisms. Aim of the Works: The aim of this study is to observe the impact of Naphthalene on bivalve mussels and to employ a large number of biomaker to discover distinct and unique patterns. For this the green mussels Perna viridis exposed to naphthalene, in order to understand the changes in marker enzymes in P. viridis haemolymph, gill, and digestive gland. Methodology: Green mussels were exposed to naphthalene for 28 days in order to assess changes in biomarker. Acid phosphatase (ACP) and alkaline phosphatase (ALP), alanine transaminase (ALT), and aspartate transaminase activity (AST) were examined in the haemolymph, gill, and digestive gland of mussels P. viridis. Results: The haemolymph has considerably higher in all marker enzymes after 28 days of naphthalene exposure. Marker enzymes were inhibited in the gill and digestive gland, and in most cases, all of the marker enzymes in the haemolymph, gill, and digestive gland were concentration dependent. The observed changes in marker enzymes which detected in the haemolymph and the other two tissues of P. viridis were statistically significant. Conclusions: The present study showed a significant association between the entire biomarkers tested in mussels exposed to naphthalene. Overall, the results indicate that haemolypmh is the most vulnerable component to naphthalene exposure when compared to tissues, and it may be employed as a bioindicator of organic pollution exposure.